Multiple Epithelial Origin Complications Following Subepithelial Connective Tissue Graft for Root Coverage. Issue 3 (25th January 2021) - Wang, Ying S.; Bissonnette, Caroline; Brett, Christopher; McNamara, Kristin K.; Tatakis, Dimitris N.
Abstract : Introduction: The subepithelial connective tissue graft (SCTG) and flap combination is a highly predictable root coverage procedure, with low complication rates. To our knowledge, this article reports the first case of two late SCTG complications, epithelial cell discharge, and subsequent epidermal inclusion cyst (EIC) formation. Case Presentation: A 35‐year‐old male presented with a 3‐mm deep Miller Class II recession defect on the mandibular right canine and mesial root of mandibular right first molar. A mild discomfort was reported at 8 weeks after envelope flap+SCTG in #27. At 4 months after the procedure, the patient presented with persistent discomfort and minimally compressible recipient site diffuse swelling with discharge, which was cytologically diagnosed as normal epithelial cells. One year postoperatively, enlargement of the lesion was seen, and excisional biopsy was performed simultaneously with SCTG in #30. The lesion was diagnosed as EIC. At 8 months follow‐up, the site healed uneventfully, the patient remained asymptomatic, and the site exhibited scar formation and no recurrence of the lesion. Conclusion: This report highlights epithelial cell discharge and EIC formation as a rare yet possible SCTG complication and emphasizes the importance of an excisional biopsy as the means to obtain a definitive diagnosis and manage this complication.